Recent Progress in Additive Manufacturing of Fiber Reinforced Polymer Composite. Issue 1 (8th October 2018) - Goh, Guo Dong; Yap, Yee Ling; Agarwala, Shweta; Yeong, Wai Yee
Abstract: Additive manufacturing (AM) has brought about a revolution in the way we can manufacture complex products with customized features. AM has paved its way in the application areas ranging from aerospace, automotive, consumer to biomedical. AM of composites has attracted special attention due to its promise in improving, modifying, and diversifying the properties of generic materials through introducing reinforcements. This review provides a detailed landscape of fiber‐reinforced composites processed via AM techniques. Different AM processes, various material formulations, and strengths and drawbacks of AM methods are discussed. Emphasis is paid to AM techniques focusing on continuous fibers, as they hold the promise of becoming the next‐generation composite fabrication methodology. The article also tries to identify the potential of AM technology for fiber‐reinforced composites and delves into challenges facing the area. Abstract : Recent progress in the development of additive manufactured fiber reinforced polymer composite, fabricated using various AM techniques, is reviewed. Several important aspects of composite materials are focussed upon, which include 1) types of reinforcements and matrices; 2) good fiber‐to‐matrix bonding; 3) fiber homogeneity; 4) fiber alignment; 5) good interlayer bonding; and 6) minimal porosity.